2015
DOI: 10.1053/j.gastro.2014.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Genes That Modulate Chronic Stress-Induced Visceral Pain in the Peripheral Nervous System

Abstract: BACKGROUNDS & AIMS Chronic stress alters the hypothalamic–pituitary–adrenal axis, increases gut motility, and increases perception of visceral pain. We investigated whether epigenetic mechanisms regulate chronic stress-induced visceral pain in the peripheral nervous systems of rats. METHODS Male rats were subjected to 1 hr water-avoidance stress each day, or given daily subcutaneous injections of corticosterone, for 10 consecutive days. L4–L5 and L6–S2 dorsal root ganglia (DRG) were collected and compared be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
147
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(155 citation statements)
references
References 37 publications
8
147
0
Order By: Relevance
“…Subsequently, visceral hypersensitivity induced by a repeated stressor or by CORT was shown to modify histone acetylation in the brain and spinal cord, leading to specific changes in pro-and anti-nociceptive gene expression. 61,62,126 DNA methylation patterns within the brain and an increase in the expression of pronociceptive neurotransmitters have also been seen in a model of stress-induced visceral pain. 61 Through the use of currently available histone deacetylase inhibitors such as TSA and suberoylanilide hydroxamic acid (SAHA), in our laboratory, we showed that subjecting male rats to water avoidance stressinduced visceral hypersensitivity could be inhibited by intracerebroventricular infusions of TSA preceding the stress exposure.…”
Section: Epigenetic Mechanisms That Contribute To Irritable Bowel Synmentioning
confidence: 95%
See 2 more Smart Citations
“…Subsequently, visceral hypersensitivity induced by a repeated stressor or by CORT was shown to modify histone acetylation in the brain and spinal cord, leading to specific changes in pro-and anti-nociceptive gene expression. 61,62,126 DNA methylation patterns within the brain and an increase in the expression of pronociceptive neurotransmitters have also been seen in a model of stress-induced visceral pain. 61 Through the use of currently available histone deacetylase inhibitors such as TSA and suberoylanilide hydroxamic acid (SAHA), in our laboratory, we showed that subjecting male rats to water avoidance stressinduced visceral hypersensitivity could be inhibited by intracerebroventricular infusions of TSA preceding the stress exposure.…”
Section: Epigenetic Mechanisms That Contribute To Irritable Bowel Synmentioning
confidence: 95%
“…The authors also found that exposing a male rat to the water avoidance stress had multiple additional effects on gene expression within the DRG including increased methylation of the cannabinoid receptor-1 promoter, causing decreased receptor expression and increased histone acetylation at the transient receptor potential cation channel subfamily V member 1 promoter, causing increased receptor expression. 126 The stress-induced visceral hypersensitivity could be reversed through targeted knockdown of the DNA methyltransferase or the histone acetyltransferase that regulated the change in receptor expression. 126 In a rodent model of chronic visceral hypersensitivity induced by neonatal maternal separation, a decrease in acetylation of histone 4 at lysine 12 in the lumbosacral spinal cord correlated with visceral hypersensitivity in adulthood.…”
Section: Epigenetic Mechanisms That Contribute To Irritable Bowel Synmentioning
confidence: 99%
See 1 more Smart Citation
“…While we cannot speculate whether this change was specific to L6 and S1 DRG neurons, or occurred generally across all DRG neurons, these findings are significant since this is the first link between altered DNA methylation and TϩE2-mediated changes in urinary function. DNA methylation and histone acetylation are known regulators of gene expression in rat nociceptive DRG neurons (15). Environmental stressors increase DNA methyltransferase 1 (Dnmt1) abundance uniquely in rat L6-S2 DRG neurons, which increases promoter DNA methylation of cannabinoid receptor 1 and decreases its expression (15).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation and histone acetylation are known regulators of gene expression in rat nociceptive DRG neurons (15). Environmental stressors increase DNA methyltransferase 1 (Dnmt1) abundance uniquely in rat L6-S2 DRG neurons, which increases promoter DNA methylation of cannabinoid receptor 1 and decreases its expression (15). This relieves repression of TRPV1 and thereby increases TRPV1 expression and visceral pain sensitivity (15).…”
Section: Discussionmentioning
confidence: 99%